Metacognition and learning: An exploratory study in medical education research (Revista Contexto & Educação, 2025)
The study analyzes the occurrence of metacognition in scientific articles in the health field, particularly those related to the academic background and performance of physicians. The main question is the following: how does metacognition relate to the physician's learning process? The objective is to investigate how metacognition is revealed to be articulated in national and international research published in articles that deal with the learning processes linked to the academic background and performance of physicians. To achieve the objective, a bibliographic research of the state of knowledge type was carried out, selecting five databases as the locus of investigation: Education Resources Information Center (ERIC), SciELO, Web of Science (WoS), Scopus and PubMed. In these databases, and based on a combination of descriptors, 17 studies were selected to constitute the research corpus. These articles, after being read in full, revealed that in 2021, the Brazilian Journal of Medical Education and the United States and Brazil have the largest number of studies. Furthermore, the target audience of the research is concentrated in medical students. In terms of metacognition and physician learning, the results indicate that questionnaires are the most widely used instruments and that metacognition appears in the research as a learning strategy and/or as a factor in medical decision-making.
Keywords: metacognitive strategies; academic background; review of studies